Investigation into the machining characteristics of composites using chemical assisted ultrasonic machining process - Bansal, Kashish (My University, 2013)
Ultrasonic Machining (USM) is one of the earliest non-traditional machining process and is a family of relatively modern material finishing and shaping processes described as chip less machining. It is a mechanical material removal process used to erode holes and cavities in hard or brittle work pieces by using shaped tools, high frequency mechanical motion and abrasive slurry. In the present study, the chemical-assisted ultrasonic machining (CUSM) method is introduced in order to improve the material removal rate and the integrity of the machined surface. For this a low concentration hydrofluoric acid solution is added to the alumina slurry. The effect of different input parameters namely Power Rating, Tool type, Slurry type, Slurry Concentration and Grit Size on the output parameters namely MRR, TWR, SR and Hardness was studied. A number of factors and their different levels are selected. Based on factors and their levels number of experiments are selected using orthogonal array. The effect of various input parameters on output parameters is analysed using statistical technique such as ANOVA. Optimization and verification of the process parameters and the modelling of the results is done by applying Regression Analysis. Main effect plot and Residual plot for significant factors and S/N ratio have been used to determine the optimal design for each output response. In the end, the effect of Chemical Assisted Ultrasonic Machining process is compared with conventional USM process on the basis of output parameters such as MRR and SR. Through various experiments and comparison with conventional results, the superiority of CUSM is verified. The material removal rate increase to 40% also the surface quality of the material was also determined..
ME
Keywords: Chemical assested ultrasonic machining (USM); material removal rate (MRR); surface roughness; ANDVA